Changes in pharyngeal airway space and hyoid bone position after Bionator treatment of skeletal Class II malocclusions - Tanaka Mioko; Seto Yoshiko; Kobayashi Sakurako (Sciendo, 2023)
The objective of this study was to investigate the treatment effectiveness of long-term Bionator use on the craniofacial pattern, nasopharynx, oropharynx, hypopharynx, hyoid bone, and cervical vertebrae in patients presenting with a skeletal Class II malocclusion involving mandibular retrognathia.